Change Management via Data Analytics for a successful Lean Transformation of Public Companies - Angelopoulos, Michail; Pollalis, Yannis (Archives of Business Research, 2021)
Data analytics is one of the biggest "revolutions" that have taken place in recent years at the business level, enabling many companies to go through a digital transformation, reducing risks and costs and making them more Agile and Lean. Data analytics is a process with heavy business relevance, companies are analyzing data - numbers mainly - and trying to determine decisions for the future based on it. Hence, severe pressure is being posed on public companies to dwindle their operational costs. A method contributing to this direction is the Lean philosophy, as through proper strategies, with its practices and tools leads to substantial resources saving. Each company possesses a unique way of integrating the principles and practices of Lean Management. In other words, there is no specific methodology, which is applicable by every business worldwide. Explicit condition for the success of Lean Management is the presence of the Effective Change Management. Data analysis is achieved by using the quantitative research method, which highlights the existence of influence as a "moderator effect" of the strategy followed by an effective change management compared to the aforementioned critical success factors (CSFs) was examined by performing interaction analysis in "IBM SPSS Amos 21, so that the parsimonious transformation is feasible. The quantitative approach is based on sample research with standardized questionnaire actualized at the two biggest Greek companies of public interest and utility purpose. The data from the participants’ responses ere inserted on a data basis «SPSS Version 23 for Windows». The findings of the research showed that human and organizational factors determine the greatest part of the effective integration of the Lean Management in public companies. The study examined, the influence of an Effective Change Management on important CSFs for a successful integration Lean Management (Lean Transformation) in Greek public companies. Also contributes to fill a research gap on the impact of Lean Management in public companies, since the vast majority of research work is focused on the private sector.